Available outdoor space and competing needs in public kindergartens in Oslo - Nilsen, Askild Hjelkerud (FormAkademisk, 2014)
To be able to plan a diverse and flexible environment in kindergartens for children from 1 to 5 years of age, available and adequate space is needed, preferably an open and coherent space adaptable to change. Hence, size itself is a factor to control and regulate to ensure that children’s needs are met. The aim of this study was to investigate how the utilization of outdoor space responded to changes in applied norms and law over time. The hypothesis was that needs for space of a more administrative nature, such as parking, have been prioritized over play area. To test this hypothesis, 201 public kindergartens in Oslo’s outer city that offer full-day service were studied. The main findings were that the gross size of kindergartens in Oslo decreased by 12.6 m2 per child for those built after 2006 compared to those built before 1975, due to legal changes in these time intervals, and that play space per child constituted more than half of this decrease. In the same time period, the reduction in space for parking and roads on the premises decreased by only 1.6%. This finding suggests that norms founded in laws win the battle over space, even if this indirectly compromises the meeting of children’s needs for an adequate outdoor play area.